Do Background Colors Have an Impact on Preferences and Catch the Attention of Users? - Anna Lewandowska; Agnieszka Olejnik-Krugly (Applied Sciences, 2021)
In recent years, our environment has become more invasive and stimulating than ever. People must choose carefully what to look for in their over-stimulated daily lives. One way to attract visual attention, which may even interrupt the cognitive task being performed, is color. However, a question arises: Does each color attract the attention of users in a similar way? In this paper, we attempt to answer this question. Our goal is to investigate whether there are colors that have a greater visual power than other colors and, thus, can capture the attention of users more strongly, independent of the background (e.g., color or image). We also discuss which mode of visual attention (divided or sustained) is particularly susceptible to such visual messages. For this purpose, a perceptual experiment was developed, in which user preferences concerning user-friendly and readable color compositions were acquired. At the same time, we measured the unconscious reactions of users related to their first impression, thus indicating the color composition which first (from a displayed pair of images) draws the attention of users. Reactions were measured using an eye tracker. As a result of this research, we found that the background color, in the case of some colors, does not have a significant impact on the perception of the visual message, even if it is intended to attract and maintain the attention of the user.